Please help thanks!!
![Please help thanks class=](https://us-static.z-dn.net/files/de0/f57ebc1ab40d60e46c14f8cc95b7a8cf.png)
So for this, you just need to combine like terms.
[tex] 2x-8y+3x^2+7y-12x\\3x^2-10x-y [/tex]
In short, the answer is the second option.
2x - 8y + 3x^2 + 7y - 12x
= 2x + - 8y + 3x^2 + 7y + - 12x
Combine Like Terms:
= 2x + - 8y + 3x^2 + 7y + - 12x
= (3x^2) + (2x + - 12x) + ( - 8y + 7y)
= 3x^2 + - 10x + - y
Answer: 3x^2 - 10x - y
Hope that helps!!!! ( Answer: 3x^2 - 10x - y, So, Letter Choice (B2), is your answer).